2019
DOI: 10.1021/acs.organomet.8b00945
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Properties, and Complex Formation of Antimony- and Bismuth-Bridged Bipyridyls

Abstract: Antimony-and bismuth-bridged bipyridyls (dipyridinostibole and dipyridinobismole; DPySb and DPyBi) were prepared by the reactions of dilithiobipyridyl with dibromophenylstibine and diiodophenylbismuthine. Xray diffraction studies of the crystal structures revealed a high planarity of the heterole ring. Cyclic voltammograms obtained in acetonitrile indicated enhanced electron affinity in comparison to a bridge-free bipyridyl. These compounds showed weak fluorescence at room temperature and visible phosphorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…The bond lengths and angles around the antimony atom in 5 are approximately the same as in linear stibole 3. Furthermore, similar bond lengths and angles have been observed among previously reported stiboles, including benzostiboles [27,35], dipyridostibole [30], and 7-tolyldinaphthostibole [31]. Table 1.…”
Section: Structure Analysissupporting
confidence: 81%
See 1 more Smart Citation
“…The bond lengths and angles around the antimony atom in 5 are approximately the same as in linear stibole 3. Furthermore, similar bond lengths and angles have been observed among previously reported stiboles, including benzostiboles [27,35], dipyridostibole [30], and 7-tolyldinaphthostibole [31]. Table 1.…”
Section: Structure Analysissupporting
confidence: 81%
“…Subsequently, they reported both the synthesis of pyridine-fused tricyclic stibole V (9-phenyl-stibolo [2,3c:5,4-c ]dipyridine) and its phosphorescence at low temperature. They also revealed that the copper complex derived from stibole V and Cu 2 I 2 (PPh 3 ) 3 displayed phosphorescence at room temperature [30]. We reported the synthesis and structural study of optically active 7-(p-tolyl)dinaphtho[2,1-b:1 ,2 -d]stibole (7-Tol-DNSb) and revealed the dynamic behavior of the binaphthyl skeleton based on the C 2 symmetry axis [31].…”
Section: Introductionmentioning
confidence: 93%
“…This compound and related antimony derivative (DPySb) possess a weak fluorescence at room temperature and an appreciable phosphorescence at 77 K with the emission maxima at λ max = 453 and 454 nm and the lifetimes τ = 1.03 and 0.26 ms for DPySb and DPyBi, respectively. Solid-phase phosphorescence was also observed for these dipyridinoheterols at 77 K. The reaction of DPyBi with Cu 2 I 2 (PPh 3 ) 3 affords the corresponding copper complex [(PPh 3 )CuI(DPyBi)-CuI(PPh 3 )] 2 , which demonstrates red phosphorescence in the solid state at room temperature [42].…”
Section: Scheme 35mentioning
confidence: 87%
“…This is likely due to the intramolecular through space interaction between the two dipyridinometallole units that are linked by Cu 2 I 2 units. [21] For DPyS1À Cu, however, the DPyS1 units linked by Cu 3 I 3 units are too distant from each other to realize similar through space interaction.…”
Section: Synthesis and Properties Of Dpys1à Cu And Dpysn1à Cumentioning
confidence: 99%